2011
DOI: 10.5603/fhc.2011.0013
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic vessel invasion detected by the endothelial lymphatic marker D2-40 (podoplanin) is predictive of regional lymph node status and an independent prognostic factor in patients with resected esophageal cancer

Abstract: Abstract:The discovery of markers to lymphatic endothelial cells and the development of novel antibodies to these markers have brought increasing attention to the lymphatics and progress in the understanding of lymphangiogenesis and cancer metastasis. In this study, we investigate the presence of lymphatic vessel invasion (LVI) detected by D2-40 immunohistochemical staining in resected esophageal cancer and correlated with clinicopathologic data and patient survival. Sixty nine patients, who had a primary rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Imamura et al [17], using D2-40 staining, revealed that positive LVI correlated with worse prognosis in univariate analysis and was an adverse independent prognostic factor for overall survival in patients classified as node negative. Our earlier study found that LVI in the entire tumor is an independent prognostic factor of both disease-free survival and overall survival [23]. This study's results show that positive itLVI and ptLVI, like lymph node metastasis, tumor depth, stage, and positive resection margin, are significantly associated with worse disease-free survival, cancer-specific survival and overall survival in univariate and multivariate analyses.…”
Section: 017supporting
confidence: 48%
See 1 more Smart Citation
“…Imamura et al [17], using D2-40 staining, revealed that positive LVI correlated with worse prognosis in univariate analysis and was an adverse independent prognostic factor for overall survival in patients classified as node negative. Our earlier study found that LVI in the entire tumor is an independent prognostic factor of both disease-free survival and overall survival [23]. This study's results show that positive itLVI and ptLVI, like lymph node metastasis, tumor depth, stage, and positive resection margin, are significantly associated with worse disease-free survival, cancer-specific survival and overall survival in univariate and multivariate analyses.…”
Section: 017supporting
confidence: 48%
“…Lin et al [22] have reported similar observations for colorectal cancer. Imamura et al [17], Tomita et al [18] and our earlier study [23] revealed that LVI in the entire tumor tissue of esophageal cancer was significantly linked with nodal metastasis. In contrast, Mori et al [15] found that only ptLVI positively correlated with lymph node metastasis.…”
Section: Discussionmentioning
confidence: 75%
“…Lymphatic vessels are the main pathways for the spread of tumor cells to regional lymph nodes (3,4,812). The shape of lymphatic vessels is very similar to that of small veins, making it difficult to distinguish lymphatic from blood vessels when they are invaded and destroyed (8).…”
Section: Discussionmentioning
confidence: 99%
“…Research into the mechanism of tumor metastasis has primarily focused on vascular vessels, with little focus on lymphatic vessels. Lymphatic vessels are important pathways for metastasis and are a primary cause of post-operative tumor recurrence (1,3,6,8). Therefore, it is of great clinical and physiological significance to discover the molecular mechanisms underlying tumor development and metastasis through lymphatic vessels and to explore ways of preventing tumor lymphatic metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…PDPN has previously been used to assess lymphatic vessel density and invasion in various types of cancer, including esophageal carcinoma (10,11). Thus, it may act as a mediator of tumor cell invasion and metastasis (12).…”
Section: Introductionmentioning
confidence: 99%